2014
DOI: 10.12816/0018706
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Intellectual Capital Components and Firm Size

Abstract: This study examines the relationship between intellectual capital components sizes listed company is enhancing the Tehran Stock Exchange. Using a quasi-experimental research and survey companies listed in Tehran Stock Exchange and the research period from 1381 to is 1390. Due to the limitations of the present study, 27 were selected to participate in the relevant period. Also according to the method of data collection, the data collected for this study, 270 years-is now. After the selection of the sample, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Also, considering the results of the 1 st to 3 rd secondary hypotheses which led to the confirmation of 1 st and 2 nd secondary hypotheses and rejection of 3 rd secondary hypothesis and also the based on the obtained information we can conclude that H0 is rejected and H1 is accepted and this indicates that the 1 st main hypothesis of the research is confirmed, that is we can conclude that there is a positive relationship between intellectual capital and market valuation indicators especially the components of physical and structural capitals. From the result of the 1 st main hypothesis it can be concluded that the finding of this research is consistent with the findings of Chen et al (2005), Wang (2011), Bani et al (2014) and has some similarities and some differences with other studies in the same field.…”
Section: Descriptive Indicators Of Variablessupporting
confidence: 90%
“…Also, considering the results of the 1 st to 3 rd secondary hypotheses which led to the confirmation of 1 st and 2 nd secondary hypotheses and rejection of 3 rd secondary hypothesis and also the based on the obtained information we can conclude that H0 is rejected and H1 is accepted and this indicates that the 1 st main hypothesis of the research is confirmed, that is we can conclude that there is a positive relationship between intellectual capital and market valuation indicators especially the components of physical and structural capitals. From the result of the 1 st main hypothesis it can be concluded that the finding of this research is consistent with the findings of Chen et al (2005), Wang (2011), Bani et al (2014) and has some similarities and some differences with other studies in the same field.…”
Section: Descriptive Indicators Of Variablessupporting
confidence: 90%
“…Many researches categorise intellectual capital into three main elements: human capital, organizational capital and customer (relational) capital (Marzo & Scarpino, 2016;Bani et al, 2014;Maditinos et al, 2011;Yang & Lin, 2009;Reed, Lubatkin & Srinivasan, 2006). Basically, the components of IC could deliver a more transparent comprehension of the concept and its impact on business performance (Choo Huang, Luther & Tayles, 2007;Marcin, 2013).…”
Section: Introductionmentioning
confidence: 99%